ANALISIS KEPUASAN PESERTA BPJS KESEHATAN TERHADAP PENGGUNAAN APLIKASI MOBILE JKN - Metya Lutviani (JURNAL LENTERA BISNIS, 2025)
This study discusses the benefits of using the JKN Mobile Application for BPJS Kesehatan participants. The JKN Mobile Application is one of the applications that continues to be developed by BPJS Kesehatan which can be downloaded by smartphone users and functions to assist JKN participants in the administration process or obtain information about the JKN-KIS program. The purpose of this study was to analyze the level of consumer satisfaction with the use of the JKN Mobile application. In this study, the researcher used a qualitative research method with a descriptive approach by interviewing five participants who used the JKN mobile application. The results of the study showed that participants were satisfied with the use of the JKN Mobile Application because with the JKN mobile application, BPJS Kesehatan participants received fast, responsive and reliable service, because this application can be accessed anywhere and anytime. However, there are still several obstacles faced by BPJS participants when they are going to use the JKN mobile application, especially in taking a queue at a specialist polyclinic, because taking a queue at a specialist polyclinic is very difficult due to the limited number of patients served each day so that BPJS participants have difficulty getting a queue number if they want to go to a specialist polyclinic and some elderly patients also have difficulty using the JKN Mobile application because elderly patients do not understand how to use gadgets. It is hoped that in the future there will be a solution provided by BPJS Kesehatan regarding the ease of service in specialist policies so that all people have the right to obtain treatment easily and quickly and for elderly patients can be given assistance for their JKN mobile registration which is assisted by health workers at each health facility.